PEMBELAJARAN QTL BERBASIS PROYEK DALAM BENTUK WEB UNTUK MENINGKATKAN MOTIVASI DAN KETERAMPILAN BERPIKIR 4C - Fitriana Eka Chandra; Fury Styo Siskawati (Prodi Pendidikan Matematika FKIP Universitas Madura, 2021)
The Covid-19 pandemic, which has swept the world for almost two, years has changed the implementation of education in Indonesia. Learning that was previously always done face-to-face has now been shifted to distance learning, which in its performance is a challenge, especially for mathematics teachers. So far, the problems faced by teachers are difficulties in making students more enthusiastic in learning during the online learning period and challenges in developing students' thinking skills. A learning model is needed that can train students so that during online learning, students can still practice improving their 4C thinking skills. This research is a descriptive study in the form of a literature review conducted by reviewing several literatures. Based on the literature review, it can be seen that one approach that can be used is a project-based Quantum Teaching and Learning (QTL) approach which can be presented in web form so that students are more motivated during the online learning period. Based on theoretical studies from several articles, it is known that learning QTL can increase students' learning motivation because QTL is taught according to students' thinking. Giving projects that are in accordance with students' interests can be added to QTL learning to train students to improve 4C thinking skills.